Thermophilic Digestion of Palm Oil Mill Effluent: Enhancing Biogas Production and Mitigating Greenhouse Gas Emissions - Anwar, Dedy; Simanjuntak, Evy Enjelina; Sitepu, Ivana; Kinda, Meiyer Marthen; Nainggolan, Ellyas Alga; Wibowo, Yudha Gusti (Universitas Diponegoro, 2024)
This study investigates the impact of thermophilic anaerobic digestion on biogas production and methane emission reduction from Palm Oil Mill Effluent (POME). Conducted under controlled conditions at 55°C and 65°C, the research aims to optimize biogas yield and reduce Chemical Oxygen Demand (COD) levels. The findings indicate that thermophilic digestion at 65°C significantly enhances biogas production, yielding 1.81 L Biogas per liter of POME over an 8-day period, compared to mesophilic conditions. Furthermore, the study demonstrates substantial COD reduction, supporting a more efficient and environmentally friendly process. By capturing methane emissions and converting them into a renewable energy source, this method aligns with global climate policies and greenhouse gas reduction targets. The integration of thermophilic anaerobic digestion into POME treatment presents a viable solution for the palm oil industry to improve waste management practices and contribute to sustainable development goals. Future research should explore large-scale implementations to maximize the environmental and economic benefits of this technology.